A Chandra study of Abell 795 – a sloshing cluster with an FR0 radio galaxy at its centre. Issue 3 (22nd March 2021) - Ubertosi, F; Gitti, M; Torresi, E; Brighenti, F; Grandi, P
ABSTRACT: We present the first X-ray dedicated study of the galaxy cluster Abell 795 (A795) and of the Fanaroff–Riley type 0 (FR0) hosted in its brightest cluster galaxy. Using an archival 30 ks Chandra observation, we study the dynamical state and cooling properties of the intracluster medium (ICM), and we investigate whether the growth of the radio galaxy is prevented by the surrounding environment. We discover that A795 is a weakly cool-core cluster, with an observed mass deposition rate ${\lessapprox} 14$  M⊙  yr −1 in the cooling region (central ∼66 kpc). In the inner ∼30 kpc, we identify two putative X-ray cavities, and we unveil the presence of two prominent cold fronts at ∼60 and ∼178 kpc from the centre, located along a cold ICM spiral feature. The central galaxy, which is offset by 17.7 kpc from the X-ray peak, is surrounded by a multitemperature gas with an average density of n e = 2.14 × 10 −2  cm −3 . We find extended radio emission at 74–227 MHz centred on the cluster, exceeding the expected flux from the radio galaxy extrapolated at low frequency. We propose that sloshing is responsible for the ICM spiral morphology and the formation of the cold fronts, and that the environment alone cannot explain the compactness of the FR0. We argue that the power of the cavities and the sloshing kinetic energy can reduce and offset cooling. Considering the spectral and morphological properties of the extended radio emission, we classify it as a candidate radio mini-halo.